2010
DOI: 10.1007/s11682-009-9085-0
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Brain Activation During Encoding and Recognition of Male and Female Faces

Abstract: Although behavioral studies have suggested that there are gender differences regarding facial recognition, the neural substrates of these differences have not been fully examined. In order to clarify them, we performed a functional magnetic resonance imaging (fMRI) experiment in which participants encoded and recognized male and female faces. Behaviorally, the facial recognition ability of men and women was similar, and was superior for female faces compared to male faces. At the neural level, widespread areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 59 publications
3
26
0
Order By: Relevance
“…FFA activity was greater under stress for women but diminished under stress for men, a relationship that was correlated with baseline testosterone but not estrogen levels (Mather et al, 2010). These findings are particularly interesting in the light of another recent study by Ino, Nakai, Azuma, Kimura, and Fukuyama (2010). They suggested that the reduced activation of women's brains during processing emotions suggest that the relevant neural systems are more efficiently recruited in women than in men.…”
Section: Activation Patterns In Males As Compared To Femalesmentioning
confidence: 57%
“…FFA activity was greater under stress for women but diminished under stress for men, a relationship that was correlated with baseline testosterone but not estrogen levels (Mather et al, 2010). These findings are particularly interesting in the light of another recent study by Ino, Nakai, Azuma, Kimura, and Fukuyama (2010). They suggested that the reduced activation of women's brains during processing emotions suggest that the relevant neural systems are more efficiently recruited in women than in men.…”
Section: Activation Patterns In Males As Compared To Femalesmentioning
confidence: 57%
“…Since performance on face recognition tasks tends to differ between the sexes (Cross, Cross, & Daly, 1971;Ino, Nakai, Azuma, Kimura, & Fukuyama, 2010;Lewin & Herlitz, 2002;Rehnman & Herlitz, 2006Shaw & Skolnick, 1994Wright & Sladden, 2003), the aim of present study was to investigate gender differences in the tendency to represent sets of faces in terms of a summary description. There is some indirect evidence to suggest that there may be gender differences in visual averaging.…”
Section: Introductionmentioning
confidence: 99%
“…An often reported finding is that females are better than males at recognizing female faces (Cross et al, 1971;Lewin & Herlitz, 2002;Rehnman & Herlitz, 2006Shaw & Skolnick, 1994Wright & Sladden, 2003), whereas male observers are sometimes better at recognizing male faces than female faces (Ino et al, 2010;Shaw & Skolnick, 1994Wright & Sladden, 2003). The owngender advantage in face recognition is generally explained in terms of differences in interest and motivation (McKelvie, Standing, St. Jean, & Law, 1993) or perceptual expertise (Lovén, Herlitz, & Rehnman, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As expected, women accurately recognized more faces than men, F(1,195) = 13.57, p b .001, d = 0.59 (M females = .39, SE = .01, M males = .33, SE = .01) and female faces were better recognized than male faces overall, F(1,195) = 43.79, p b .001, d = 0.36 (M females = .39, SE = .01, M males = .34, SE = .01), as is often found (Ellis, Shepherd, & Bruce, 1973;Godard & Fiori, 2010;Ino, Nakai, Azuma, Kimura, & Fukuyama, 2010;Rehnman & Herlitz, 2007). However, there was a significant interaction of participant gender and test face gender such that women recognized female faces much better than male faces (d = 0.72), but men recognized female and male faces with similar accuracy (d = 0.12), F(1,195) = 23.56, p b .001, difference in d = 0.60.…”
Section: Effects Of Participant Gender Orienting Task and Recognitimentioning
confidence: 66%